Inverse Correlation of Th2-Specific Cytokines with Hepatic Egg Burden in S. mansoni-Infected Hamsters - Russ, Lena; von Bülow, Verena; Wrobel, Sarah; Stettler, Frederik; Schramm, Gabriele; Falcone, Franco H.; Grevelding, Christoph G.; Roderfeld, Martin; Roeb, Elke; Justus Liebig University Giessen (My University, 2024)
Schistosomiasis, a parasitic disease caused by Schistosoma spp., affects more than 250 million people worldwide. S. mansoni in particular affects the gastrointestinal tract and, through its eggs, induces a Th2 immune response leading to granuloma formation. The relationship between egg load and immune response is poorly understood. We investigated whether the quantity of parasitic eggs influences the immune response in S. mansoni-infected hamsters. The hepatic and intestinal egg load was assessed, and cytokine expression as well as the expression of three major egg-derived proteins were analyzed in monosex- and bisex-infected animals by qRT-PCR. Statistical correlations between egg load or egg-derived factors Ipse/alpha-1, kappa-5, and omega-1, and the immune response were analyzed in liver and colon tissue. Surprisingly, no correlation of the Th1 cytokines with the hepatic egg load was observed, while the Th2 cytokines Il4, Il5, and Il13 showed an inverse correlation in the liver but not in the colon. A longer embryogenesis of the parasitic eggs in the liver could explain this correlation. This conclusion is supported by the lack of any correlation with immune response in the colon, as the intestinal passage of the eggs is limited to a few days.
Keywords: ddc:610